Analysis of factors affecting demand for safe and quick loans at PT Pegadaian (Persero) main office in Medan City - Edo Juanda Butar-Butar; Andre Fitriano; Jeremia Barus; Efendi Sadly (Privietlab, 2023)
The purpose of this research is to determine whether or not Fast Secured Credit (KCA) demand is affected by customers’ income, the number of dependents they support, and their level of education. One hundred people were selected at random and through convenience sampling for this study. A quantitave approach was taken for this study. The test result show that the income variable, dependents, and education level have a positive and significant effect on demand for credit. It is recommended that if the customer’s income increases, the community should save money, if one day there is an urgent need it can be resolved.